(untitled) (Transport systems and technologies, 2021)
The paper presents modern concepts of the contact fatigue crack occurrence in the railhead. Numerical simulation of the contact interaction between rails and rolling stock wheels by finite elements method are presented. During the simulation, the problem was solved in elastic and elastic-plastic formulations. We considered R65 rail profile and standard railway wheels. The conditions for the rail–wheel interaction corresponded to train movement on the straight section of the track without slipping. The modern life assessment methodology involves the calculation of the material damage increment at each point of the element as the load varies over time, and subsequent summation of this damage. Upon reaching the ultimate value of the total damage, the structural element is believed to lose its load-carrying capacity, i.e. a crack is formed in it. Despite the substantial simplification of the real problem, the computational costs for the implementation of such methods for predicting the durability will be unnecessarily high. In this regard, we propose the simplified method of the durability calculation.